2021
DOI: 10.14411/fp.2021.013
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular description of Allocreadium apokryfi sp. n. (Digenea: Allocreadiidae) from native Labeobarbus aeneus (Cyprinidae) in South Africa, including notes on its biology, evolutionary history and an updated key of African Allocreadium

Abstract: Adult trematodes of Allocreadium Looss, 1900 (Digenea) infect the intestine of mostly freshwater fishes in Asia, Europe, Africa and the Americas. During routine parasitological surveys in the Vaal River system, adult trematodes were collected from the intestine of smallmouth yellowfish, Labeobarbus aeneus (Burchell). The trematodes were confirmed to represent a member of Allocreadium and did not match any existing taxon. Therefore, they are described as a new species, Allocreadium apokryfi sp. n. The morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
3
9
1
Order By: Relevance
“…The NJ tree showed the same topology within the clade of Allocreadium as that presented in study of Dos Santos et al (2021), but statistical support for such a division (subclades h and b – g ) was lower than 50% (Figure 2c). The African species Allocreadium apokryfi recently described by Dos Santos et al (2021) had a variable position on the reconstructed phylogenetic trees (Figures 2a–d). In the original description, A. apokryfi was nested between the branches of A. pseudoisoporum ( Allocreadium sp.)…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The NJ tree showed the same topology within the clade of Allocreadium as that presented in study of Dos Santos et al (2021), but statistical support for such a division (subclades h and b – g ) was lower than 50% (Figure 2c). The African species Allocreadium apokryfi recently described by Dos Santos et al (2021) had a variable position on the reconstructed phylogenetic trees (Figures 2a–d). In the original description, A. apokryfi was nested between the branches of A. pseudoisoporum ( Allocreadium sp.)…”
Section: Discussionsupporting
confidence: 71%
“…In the original description, A. apokryfi was nested between the branches of A. pseudoisoporum ( Allocreadium sp.) and A. gotoi based on the BI and ML models with equivocal support for such a resolution (0.8 posterior probabilities/53%) (Dos Santos et al 2021). Such topology corresponds to the tree reconstructed with NJ method but was not supported by us (Figure 2c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these reports are from North America and Europe. In Africa, although the adults of allocreadiids, bucephalids and gorgoderids occur in freshwater fishes (Dos Santos et al, 2021; Paperna, 1996; Zhokhov, 2010), their intermediate hosts remain largely unknown. In the current study, gorgoderid larvae were found in Coelatura spp.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of close relationships of trematodes from Eurasian and North American continents have been observed for gorgoderoids. For example, detailed phylogenetic analysis of Allocreadiidae indicated such relationships, where North American species belong to a terminal clade, sister to Asian and European species within this family (Soldánová et al, 2017;Petkevičiūtė et al, 2018;Atopkin et al, 2020;Faltýnkova et al, 2020;Vainutis et al, 2021;Bogatov & Vainutis, 2022). However, lack of molecular data on species, closely related to C. neilgherriensis and P. limi as well as for type-species of Chelatrema is a barrier to clarify these relationships.…”
Section: Discussionmentioning
confidence: 99%